Pilonidal abscess in the breast: a case report - Lahiri, Rashmi (Oxford University Press, 2014)
Pilonidal sinus is a common entity, most often occurring in the natal cleft. Pilonidal sinus with abscess formation has also been described in hairdressers in the interdigital space. We report a case of pilonidal abscess of the breast in a hairdresser, a rarely reported site, which requires awareness on the clinician's part of this occupational risk, for appropriate management and post-surgery advice on prevention. It is particularly important to impart such information to the reporting pathologist who is key to making this histological diagnosis.